Ashitaba (Angelica keiskei) leaves extract prevents spatial memory impairment in male balb/c mice (Mus musculus) with brain aging - Indah Mira Tiaraputri Wijaya; Wimpie Pangkahila; Thomas Eko Purwata (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2021)
Background: Memory impairment is one of the symptoms of aging process which can be caused by free radicals or oxidative stress. Antioxidants such as flavonoids are compounds that can inhibit reactive oxygen species (ROS). Ashitaba (Angelica keiskei) is one of the natural compound that contains high flavonoids. The purpose of this study was to prove that Ashitaba (Angelica keiskei) leaves extract prevents spatial memory impairment in male Balb/c mice (Mus musculus) with brain aging Methods: Experimental randomized pretest-posttest group using 26 mice, aged 3 months, healthy (active and willing to eat), weighing 20-30 grams. Mice were induced with oral D-Galactose of 300 mg/kgBW/day for 4 consecutive weeks to achieve the brain aging condition. Control group treated with placebo (2 ml of aquabidest), and another group was treated with Ashitaba leaves extract of 20 mg/kgBW/day. Before and after treatment for 28 days, spatial memory were examined using the Morris Water Maze method. Results: The results showed a significant decrease in probe test (from 72,9±5,69% to 40,8±5,10%; p<0,001) and the number of platform crossings (from 7,37±0,527 times to 4,50 ± 0,771 times; p<0,001) in the control group suggesting that D-Galactose-only treatment impaired spatial memory. In contrast, the group treated with D-Galactose and Ashitaba leaves extract, there was no change in probe test (from 72,1±5,9% to 66,0±6,72%; p>0,05) and number of platform crossings (from 7,65±0,881 times to 6,98±0,787 times; p>0,05). Conclusion: This study indicated that Ashitaba (Angelica keiskei) leaves extracts prevented spatial memory impairment in male Balb/c mice (Mus musculus) with brain aging.